Impact of KVK Training on Farmers Adoption Behaviour and Knowledge Gain - Kumbhare, N.V.; Khonde, S.R. (Indian Journal of Extension Education, 2009)
The study conducted in seven villages of Wardha district where the KVK run by Dr. Punjabrao Deshmukh Krishi Vidyapeeth, Akola is carrying out its activities. The data collected from 150 randomly selected farmers revealed that half of the farmers (59 percent) adopted the recommendation of KVK at medium level, whereas, other half of the sample population fell into the categories of low and high level with equal percentage i.e. 25percent each. The study also revealed that 66 percent respondents gain knowledge of improved practices at medium level, whereas, 20 per cent and 14 per cent respondents gain knowledge after training at low and high level respectively. The characteristics of the respondents like education, land holding, social participation, socio-economic status, and farmer's involvement in agricultural programme are found to be significantly correlated with the impact of KVK training on the adoption behaviour and knowledge gain of the farmers. Also the situational, psychological and communication variables showed significant relationship with the impact of training on adoption behaviour and knowledge gain.